Rules and Application of Trading Robot on Sharia Stock in Indonesia - Julistiyan, Ridoni; Hidayatulloh (University of Darusssalam Gontor, 2023)
This research began with the anxiety of the Islamic investor community regarding the decision of the Indonesia Stock Exchange to allow exchange members to use the trading robot feature (automated ordering). This policy raises a new problem for the practice of trading sharia stocks using trading robots. Therefore, this research aims to discover the practice of trading robot tools in the sharia stock market. Besides, the research also aims to explore the views of Islamic law on sharia stock investors who practice buying and selling sharia shares with trading robots, with the research object being PT Indo Premier Sekuritas. This type of empirical juridical research analyzes the mechanism of the practice of sharia stock transactions in the secondary market with trading robots associated with several provisions in a regulation. The data collection method used in this legal research is the method of observation, interviews, and documentation. The results of this research stated that the practice of trading robots at PT Indo Premier Sekuritas is permissible according to sharia principles for some reasons. First, this trading robot is used as an intermediary or instrument to convey information. Second, the investors must understand the information contained in the trading robot. On the other side, trading robots can only be legal if investors fully understand how trading robots work because their ignorance can plunge them into the practice of maysir or gambling. Currently, there are no strict regulations governing trading robots in Indonesia. Although there is no legal regulation, it is not an act that is against the law because trading robots are only tools that make it easier for traders and investors to automate transactions. However, investors can be suspected of criminal acts if the trading robot is vulnerable to market manipulation and marketed by providing profit guarantee promises. More dangerously, the company which conducts the business of raising investment funds does not get a permit from the Indonesia Stock Exchange.